Relative match load in young professional soccer players during soccer-7 and soccer-11 - Rabano-Munoz, A.; Suarez-Arrones, L.; Requena, B.; Asian-Clemente, J. (International Journal of Sports Medicine, 2024)
The aim of this study was to analyze the differences in internal and external load during Soccer-7 and Soccer-11, comparing positional requirements and neuromuscular fatigue in both modalities. Twenty-four young soccer players were monitored in Soccer-7 and Soccer-11 matches using global positioning systems. Total distance covered (TD), distance covered at high speed (HSR), distance covered at very high speed (VHSR), peak speed, accelerations (Acc) and decelerations (Dec) and rate of perceived exertion (RPE) were recorded differentiating between central backs (CB), midfielders (MF), external players (EX) and forwards (FW). Neuromuscular fatigue were assessed using a jump test. During Soccer-11, players showed significantly higher TD, HSR and VHSR, with low Acc and greater RPE compared with Soccer-7. During Soccer-11, all positions recorded significantly greater TD, distance at HSR and at VHSR than Soccer-7. In terms of playing position, CB, MF and FW achieved significantly higher Peak Speed during Soccer-1, but there was no difference for EX. During Soccer-7 all positions performed significantly higher numbers of Acc. Although the Soccer-7 modality is considered an optimal format for the development of young soccer players, there is a significant difference in match running activity for all playing positions with respect to the Soccer-11 format.